Engines of Abolition: The Second Great Awakening, Higher Education, and Slavery in the American Northwest. - Thomas, Trevor (Kansas State University. K-State Libraries, 2016)
The essay “Engines of Abolition: The Second Great Awakening, Higher Education, and Slavery in the American Northwest” analyzes the link between religious revivalism, higher education, and abolitionist tendencies in the states of the former Northwest Territory. It will argue that fired with the moral mandates of the Second Great Awakening, institutions of higher learning founded by evangelical abolitionists often became centers of anti-slavery sentiment. In the years prior to the American Civil War, universities, colleges, and seminaries founded during the Second Great Awakening developed a number of characteristics that profoundly influenced the course of the abolitionist movement. This essay relies on newspaper articles, university-sponsored histories, writings by Southern intellectuals, sermons from revivalist ministers, lectures from university professors, and autobiographies from prominent participants in the Second Great Awakening.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Citation: Thomas, T. (2016). “Engines of Abolition: The Second Great Awakening, Higher Education, and Slavery in the American Northwest." Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Protestantism; Abolitionism; American Northwest; Second Great Awakening; Oberlin College; Lane Seminary